Anomalously low twist and bend elastic constants in an oxadiazole-based bent-core nematic liquid crystal and its mixtures; contributions of spontaneous chirality and polarity. Issue 5 (7th December 2017) - Srigengan, S.; Nagaraj, M.; Ferrarini, A.; Mandle, R.; Cowling, S. J.; Osipov, M. A.; Pająk, G.; Goodby, J. W.; Gleeson, H. F.
Abstract : The splay, twist and bend elastic constants of an oxadiazole based bent core liquid crystal and it's mixtures have been measured across the entire nematic range. Abstract : The splay, twist, and bend elastic constants of an oxadiazole based bent-core liquid crystal have been measured as functions of temperature throughout the nematic phase. The splay elastic constant ( K 11 ) behaves similarly to other bent-core systems, though it exhibits rather high values, varying between 8–14 pN. Further, anomalously low, temperature-independent values of both the twist and bend constants ( K 22 and K 33 ) are found. The combination of such low values of both constants (∼0.15 pN and ∼1.2 pN) and temperature independence has not been observed in any type of nematic material previously. This unusual behaviour has been further investigated using two independent theoretical approaches; a molecular theory based on atomistic simulations of the real molecular structure and an analytical molecular-field theory. Computational calculations show good agreement with the experimental results for both the twist and bend constants. The statistical theory introduces a term related to chiral fluctuations that affects the twist constant, while the inclusion of polarity is known to explain low values of the bend constant. The additional terms enable one to understand the origin of the low values of both elastic constants and to describe their weak temperature dependence. It also offers an explanation for the spontaneous chiral segregation observed in some nematic bent-core systems. Mixtures of this unusual oxadiazole material are made with another similar material (C5-Ph-ODBP-Ph-OC12) that has been extensively studied that exhibits somewhat higher twist and bend elastic constants to explore the behaviour as a function of concentration.